IMPROVING STUDENTS’ VOCABULARY THROUGH MEDIA APPLICATION ONLINE ‘HELLO ENGLISH’ AT CLASS X - Nur Ismiati; Asep Kurniawan (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Banten, 2019)
English is an International language that is use comunication between country, Becouse the important of English in Indonesia. Makes the curriculum in the country is obliged to follow the standard of international language.Thus many tool herefore there are lots of methods and media to learn English, especially in this technological era. There are so many interesting information and learning systems. Especially learning by using the online media application 'Hello English' will be very helpful in learning and memorizing vocabulary every day, There is always a message notification on this smart telephon. Making learning fun and not boring, In this application not only messages in words, but there are games, speaking, dictionaries and grammar in English.Result of the research show that using Media Aplication Online ‘Hello English’. Besed on the research of cycle I and cycle II that mean score in cycle I is 71,5 with percentage of passing KKM is 35%. In cycle II is 83 with percentage of passing KKM is 85%. So, Media Aplication Online ‘Helo English’ is effective and enjoyable to improve the students’ vocabulary achievement. the target of ClassroomAction Research (CAR) success, which above 24% students that could pass the KKM. Automatically, it can be said that the Classroom Action Research (CAR) is success and cycle could be stopped.